Приключения Алисы в Стране Чудес - Кэрролл Льюис (Юнацтва, 1992)
В вып. дан. г. изд. 1991 Экземпляры: КР (20020330) / Инвентарный номер: у41740 / Цена: 36.00 / Сис.шифр: И(Англ) / Авт.знак: К 98 / ГРНТИ: 17 / ББК: 84(4/8)